Using Principal Component Analysis to create an index of financial conditions in Spain. Differences by firm size and industry - Juan A. Román-Aso; Fernando Coca Villalba; Vanessa Mastral Franks; Irene Bosch Frigola (ZBW - Leibniz Information Centre for Economics, 2021)
In the last decades, a large number of academic contributions have investigated the access to credit from a great variety of perspectives. The aim of this paper is to develop an index of financial conditions to contrast subsequently, the impact of firm size and industry on it according to the information asymmetric theory. To that end, we implement a Principal Component Analysis with a database made up of 233 Spanish freelancers and MSMEs in 2018. This technique permits us to gather the objective facts and subjective perceptions of the surveyed by detecting common elements in their responses. Once components are identified, we run statistical tests to find out if firm size and industry explain the differences amongst companies. Our outcome only proves the theory for firm size, meanwhile the hypothesis remains unclear for industry
Keywords: G20; G30; M21; M41; 330; Index of financial conditions; Principal Components Analysis; Asymmetric information